Biodiversity and agriculture: A review of the evidence - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
While agri-food systems today provide enough food globally, they have been unable to provide the basis for sufficiently diverse and healthy diets, with a persistent underproduction of a range of nutritious foods like fruits, nuts, vegetables, beans and pulses. Meanwhile, agriculture is also the single largest driver of environmental degradation. These two challenges are linked through the common solution space of biodiversity.